Breeding for grain yield in mungbean (Vigna radiata L. Wikzek). - Quah, S. C. (Penerbit Universiti Pertanian Malaysia, 1984)
Although mungbean (Vigna radiata (L) Wikzek) was introduced into West Malaysian (formerly Malaya) as early as 1817,it has yet to be developed into a promising crop for cultivation by farmers in the country. This is partly due to its inherent poor grain yield and the un-synchronized nature of its flowering habit which necessitates several harvestings in order to achieve maximum yield. Yet another reason is the fact that this crop is very labour intensive and requires good management. Inspite of all these disadvantages,mungbean deserves to be popularized in Malaysia because it is a very good sources of both protein and the essential amino acid,lysine. As such,a breeding program was initiated in Universiti Pertanian Malaysia in 1979 with the twin objectives of improving the grain yield of this crop and to select better plants which have synchronous flowering habit. Hybridization began in 1979 and the crosses were progressed through 1980 and 1981. Heterosis was observed in almost of the 32 crosses for grain yield and other agronomic characters studied. Mean values for grain yield and other agronomic characters studied were considerably larger in the F2 and F3 hybrid populations than in the parental varieties when grown in 1980. In 1981,the F3 and F4 hybrids were found to have a slightly lower grain yield when compared to their parents. They were,however,shorter,had a lesser amount of vegetative matter and more but slightly smaller seeds. An additional advantage is that these hybrids had a higher harvest experiments will be discussed in relation to existing varieties.